Emerging trends and new developments in global research on artemisinin and its derivatives - Yu Lai; Huize Zhang; Xi Chen (Heliyon)
Background: The World Health Organization recommends the use of artemisinin (ART) and its derivatives for malaria treatment. Furthermore, these compounds exhibit encouraging pharmacological effects for the treatment of several diseases. Nevertheless, ongoing antimalarial treatment efforts have been significantly hindered by the emergence of drug resistance. A systematic evaluation and analysis of relevant studies may yield insights to help resolve this dilemma and reveal options for future research. Purpose: The objective of this study was to provide researchers with a comprehensive synopsis of the advancements made in the study of ART and its significant derivatives, as well as to visually present the data and provide insightful observations that can inform subsequent investigations in this domain. Methods: We searched the Web of Science Core Collection for relevant studies published by December 31, 2023. The research hotspots and frontiers pertinent to this field in terms of countries, institutions, authors, journals, references, and keywords were ascertained through scientometric analysis via CiteSpace software. Results: This study included an extensive assemblage of 12,985 data points, and the findings suggest that ART and its derivatives have garnered considerable interest among scientists. Prolonged international collaboration has fostered progress in this research field. ''Antimalarials,'' ''synthesis,'' ''drug resistance,'' and ''Plasmodium vivax'' are areas of intense research. Potential areas for future investigations may include ''proliferation,'' ''oxidative stress,'' ''pathways,'' and ''mechanisms.'' Conclusion: This study offers a comprehensive compendium of the developments and trends in the relevant research field over the past fifty years. Since pharmaceutical drug synthesis can influence both drug efficacy and cost-effectiveness, ongoing efforts to improve drug synthesis are warranted. Although the advent of novel therapeutic approaches has partially mitigated drug resistance, further investigations into the underlying mechanisms are needed. While better treatments for malaria have been developed, the therapeutic potential of ART and its derivatives for numerous additional important diseases is also possible, and future research in this area can lead to dramatic improvements in health.